Unhealthy mind in a healthy body: A criticism to eliminativism in psychopathology - Mancini, Francesco; Mancini, Alessandra; Castelfranchi, Cristiano (Frontiers in Psychiatry, 2022)
In this article we criticize the thesis “The diseases we treat are diseases of the brain”. A first criticism is against the eliminativist perspective and in favor of a perspective that is still reductionist but emergentist and functionalist. In a second part, we try to answer the question “under which conditions can we consider this statement legitimate?”. We argue that only those mental disorders whose neural substrate has clearly neuropathological characteristics, i.e., anomalies with respect to the laws of good neural functioning, can be considered “brain diseases.” We propose that it is not sufficient to observe a simple difference between the brains of people with psychopathology, that is, with anomalies with respect to the laws of good psychological functioning, and that of people without psychopathology. Indeed, we believe it is a categorical error to postulate a neuropathology starting from a psychopathology. Finally, we summarize some research that shows how purely psychological interventions can reduce or eliminate the differences between the brains of people with or psychopathology and those of people without.